2016
DOI: 10.1021/acs.jpcb.6b01185
|View full text |Cite
|
Sign up to set email alerts
|

Low-Density Water Structure Observed in a Nanosegregated Cryoprotectant Solution at Low Temperatures from 285 to 238 K

Abstract: Liquid water structure is defined by its molecular association through hydrogen bonding. Two different structures have been proposed for liquid water at low temperatures, low density liquid (LDL) and high density liquid (HDL) water. Here we demonstrate a platform which can be exploited to experimentally probe the structure of liquid water in equilibrium at temperatures down to 238 K. We make use of a cryoprotectant molecule, glycerol which when mixed with water lowers the freezing temperature of the solution n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 87 publications
6
21
0
Order By: Relevance
“…The time resolved DL decays were modelled as compressed hyperbolas [ 54 55 ] and analytically de-convolved in order to obtain rate constant distributions. The present results not only confirm the previous ones obtained by the authors on other aqueous solutions, but they are in agreement with computer simulations performed by other authors too [ 25 ].…”
Section: Introductionsupporting
confidence: 93%
See 3 more Smart Citations
“…The time resolved DL decays were modelled as compressed hyperbolas [ 54 55 ] and analytically de-convolved in order to obtain rate constant distributions. The present results not only confirm the previous ones obtained by the authors on other aqueous solutions, but they are in agreement with computer simulations performed by other authors too [ 25 ].…”
Section: Introductionsupporting
confidence: 93%
“…It was found that glycerol and water form hydrogen bonded glycerol-rich and water-rich clusters, postulating that such nanosegregation allows water to form a low density structure that is protected by an extensive and encapsulating glycerol interface. Moreover in Literature [ 25 ] it is reported that the glycerol-rich and water-rich clusters are unchanged upon cooling. According to Towey and co-workers [ 25 ] the temperature instead affects the tetrahedrality of the water network that can be quantified by measuring the included angle formed by three water oxygen atoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the physical properties of glycerol and its interactions with water have been studied extensively, the H-bond patterns of glycerol-water mixtures are much less reported at a molecular level. Neutron scattering 79 and molecular dynamics simulations 80 suggest that glycerol and water form clusters depending on mixing ratios which is directed by intramolecular and intermolecular hydrogen bonding between the two systems. Very recently a hypothesis connecting the freezing of aqueous solutions and chemical stability of amorphous pharmaceuticals have invoked water clusters, 81 and the aforementioned neutron scattering and molecular dynamics calculations were used as evidence in this intriguing suggestion.…”
Section: Strong Ionic Hydrogen Bonds In Glycerolmentioning
confidence: 99%